1992
DOI: 10.2535/ofaj1936.69.1_35
|View full text |Cite
|
Sign up to set email alerts
|

On the Organization of the Plexus lumbalis. I. On the Recognition of the Three-Layered Divisions and the Systematic Description of the Branches of the Human Femoral Nerve.

Abstract: The arrangement of the nerve bundles at the branching point of the femoral nerve (F), the interrelations of the branches each other and toward other nerves in the anterior region of the thigh, and the patterns and the anatomical features of both the running courses and the distributions of the branches were macroscopically studied, whereby some special findings were observed and the following results were obtained: 1) The periphery of the femoral nerve was fundamentally divided into superficial-deeply arranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
2
20
1
Order By: Relevance
“…Such branching pattern of the femoral nerve is similar to the present study. Aizawa (1992) reported that the medial cutaneous nerve branches and the vastus medialis, vastus intermedius, vastus lateralis, and rectus femoris nerves were arranged medially to laterally. This pattern is consistent with the present study with the exception that the intermediate cutaneous nerve of the thigh and the saphenous nerve lay between the medial cutaneous nerve of the thigh and the nerve to the vastus medialis, whereas Gustafson et al did not mention the intermediate cutaneous nerve of the thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Such branching pattern of the femoral nerve is similar to the present study. Aizawa (1992) reported that the medial cutaneous nerve branches and the vastus medialis, vastus intermedius, vastus lateralis, and rectus femoris nerves were arranged medially to laterally. This pattern is consistent with the present study with the exception that the intermediate cutaneous nerve of the thigh and the saphenous nerve lay between the medial cutaneous nerve of the thigh and the nerve to the vastus medialis, whereas Gustafson et al did not mention the intermediate cutaneous nerve of the thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the hypothesized rotation of nerves (see the Introduction) was likely to occur postnatally as well as in the late-stage fetuses. Aizawa (1992) classified human femoral nerve branches into three types, and provided an excellent schema regarding the rotation of the femoral nerve. However, the origin of the deep femoral artery in the lateral side of the mother artery in fetuses might not support the hypothetical medial rotation: the lateral rotation may be required to move the origin to the posterior aspect of the femoral artery.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fetal hip joint position, some Japanese anatomists have hypothesized that a long axis of the dermatomes and myotomes (segmental nerve supplying areas) in the human lower extremity is twisted or rotated "medially" at the hip joint (Aizawa, 1992;Ogoshi et al, 2001;Kodama, 2000;Kawashima and Sasaki, 2010). According to their understanding, not only the femoral nerve branches but also the iliofemoral ligament in adults suggests the twisting or rotation in the "fetal period".…”
Section: Introductionmentioning
confidence: 99%
“…In an excellent description of the peripheral nerves of the lower limb, Aizawa (1992) classified human femoral nerve branches into three layers, and provided an excellent schema regarding the rotation of the femoral nerve. Although the twisting lower limb has thus been disclosed fragmentary, the anatomical representation between the muscles and nerves on the twist in entire lower limb has never attempted until our report .…”
Section: How Should the Twisting Of The Human Lower Limb Be Interpreted?mentioning
confidence: 99%
“…Therefore, most anatomists, especially Japanese gross anatomists, have observed and discussed anatomical structures and their morphogenesis on the basis of the vertebrate body plan, as described in studies on the limb girdle and forelimb (Aizawa, 1992;Aizawa et al, 1995Aizawa et al, , 1996Aizawa et al, , 1999Akita, 1992aAkita, , 1992bAkita et al, 1992Akita et al, , 1994Akita et al, , 1995Akita et al, , 1999Akita et al, , 2002Arakawa et al, 2005;Aung et al, 2001;Chiba, 1983Chiba, , 1984Chiba, , 1986Chiba, , 1992Chiba et al, 1994;Homma and Sakai, 1991Honma et al, 1998;2003Horiguchi, 1980Horiguchi, , 1981Horiguchi, , 1986Kasai and Yamamoto, 1996;Kasai and Chiba, 1980;Kasai et al, 1989aKasai et al, , 1989bKato andSato, 1978, 1984;Kato, 1989;Kida and Ishida, 1989;Kodama et al, 1992aKodama et al, , 1992bKoizumi, 1989;Koizumi andSakai, 1995, 1997;Koizumi et al, 1999;Kudoh et al, 1999;Kudoh and Saki, 2007;Okamoto et al, 2004;Sato K, 1980;…”
Section: Introductionmentioning
confidence: 99%